2013
DOI: 10.1002/lt.23665
|View full text |Cite
|
Sign up to set email alerts
|

Improved Waiting-List Outcomes in Argentina After the Adoption of a Model for End-Stage Liver Disease-Based Liver Allocation Policy

Abstract: In July 2005, Argentina became the first country after the United States to introduce the Model for End-Stage Liver Disease (MELD) for organ allocation. In this study, we investigated waiting-list (WL) outcomes (n 5 3272) and post-liver transplantation (LT) survival in 2 consecutive periods of 5 years before and after the implementation of a MELD-based allocation policy. Data were obtained from the database of the national institute for organ allocation in Argentina. After the adoption of the MELD system, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 22 publications
3
35
1
5
Order By: Relevance
“…Argentina has led the region in issues related to liver allocation (22,27). Five hospitals in Buenos Aires respond to more than 80% of the transplant activity in the country, including adult, pediatric, split, and living-related liver transplantation.…”
Section: Types Of Liver Transplants Technical Aspects Of Surgery Anmentioning
confidence: 99%
“…Argentina has led the region in issues related to liver allocation (22,27). Five hospitals in Buenos Aires respond to more than 80% of the transplant activity in the country, including adult, pediatric, split, and living-related liver transplantation.…”
Section: Types Of Liver Transplants Technical Aspects Of Surgery Anmentioning
confidence: 99%
“…To estimate HCV genotype distribution, data from over 200 treated patients was used [16] . Genotype 1 (G1) subtypes distribution was calculated using data from another study [5] .…”
Section: Methodsmentioning
confidence: 99%
“…Data from the national organ registry for the years 1999 to 2013 showed that the percentage of liver transplant in HCV patients was 22.0% before adoption of model for end stage liver disease (MELD) based allocation and 22.4% after MELD implementation [15,16] . Database from the Pan American Health Organization allow us to estimate the diagnosed population based upon data for HCV positive blood donors [7] .…”
Section: Methodsmentioning
confidence: 99%
“…Cejas et al (O‐37) presented Argentinean Transplant Society data that identified a competitive advantage for candidates who received wait‐list prioritization through MELD exception points. Argentina was the first country to follow the United States in implementing a MELD‐based LAS . In their study of all transplant candidates from 2005 to 2011, patients who received MELD allocation priority exceptions had increased access to transplantation, decreased wait‐list mortality, and better posttransplant survival than patients who underwent transplantation with an equivalent physiological MELD score or had been denied prioritization.…”
Section: Allocationmentioning
confidence: 99%